Investigating How Risk Management Evolved in BP and IBM Over the Last Decade (from 2003 to 2012) - CAO, XU (2013)
This paper outlines the evolution of risk management for BP and IBM over the last ten years. Risk is prevalent in all organisational activities as it can affect the the achievement of organisational objectives. Risk management is a core essential integrated part of an organisation’s strategic management. It is the process where organisations can do risk controlling in line with the organisations’ objectives to achieve the long-term profits across the whole business activities. It should address all the risks surrounding the organisation’s activities past, present and future. Risk management has evolved over decades; risk management takes the top place of the global corporate agenda (KPMG, 2013). In order to get a deep understanding of how the risk management evolved over the last decade, this research will give a detailed investigation of risk evolution for BP and IBM over the last ten years, this investigation will focus on four key perspectives the risk management related of risk disclosure, risk management process, chief risk officer, risk committee and audit committee.